AN EVALUATION OF SPEAKING MATERIALS IN “LIFE” TEXTBOOK FROM THE PERSPECTIVES OF EFL STUDENTS AND LECTURERS - Eunike Aurelia; Y.G. Harto Pramono (Magister Scientiae, 2023)
“Life” B1+ English textbook published by National Geographic Learning has been used for some years by the English Language Education Study Program, Faculty of Teacher Education, Widya Mandala Surabaya Catholic University as the main learning resource for the English Integrated Course (EIC). One of the language skills taught in EIC is speaking. Therefore, it is important to evaluate the appropriateness of the materials for supporting speaking skills. Moreover, so far, no study has investigated this issue. Thus, this study evaluated speaking materials from the perspectives of students and lecturers. The evaluation was performed on the basis of an evaluation checklist adapted from Bao (2013). It contains seven aspects: linguistic support, content-based learning, affective support, skills support, variety of materials, flexibility of materials, and overall expectations of students and lecturers. The students and lecturers were asked to choose from the 4 options provided whether they strongly disagreed, disagreed, agreed, or strongly agreed with the evaluation indicators in the checklist. The results of the study revealed that the speaking materials in the “Life” textbook are appropriate according to the perspectives of students and lecturers.  The students and lecturers agreed that the speaking materials were relevant to students’ needs to improve their speaking skills and increase their interest in further English learning. The study concludes that the speaking materials in the “Life” B1+ English textbook are appropriate and recommended for future use.